Effect of Robot Assistive Therapy on Hand Functional Ability in Stroke Patients: Meta-Analysis - Haris Sutopo; Bhisma Murti; Argyo Demartoto (Journal of Epidemiology and Public Health, 2023)
Background: Stroke is a neurological deficit disease caused by bleeding or blockage of blood vessels in the brain which can cause disability or death. Vascular injuries cause various neurological disorders, motor disorders and functional disorders of the hands which are very necessary to carry out daily activities. Robot Assistive Therapy as a breakthrough in stroke rehabilitation technology can be used as an alternative therapy method for post-stroke rehabilitation. This study aims to determine the effectiveness of the use of robotic assistive therapy and conventional therapy on the functional abilities of stroke patients' hands. Subjects and Method: This study used a systematic review and meta-analysis design using the PRISMA flowchart guidelines and the PICO model (Population = Stroke patients. Intervention = Robot Assistive Therapy. Comparison = Conventional therapy. Outcome = Hand functional ability). The article search process was carried out using databases from PubMed, Science Direct, AJOT, Springer Link, and Google Scholar. The keywords used are “Robot Assistive Therapy” AND “stroke” AND “hand function” AND “randomized controlled trial” AND “Fugl Meyer Assessment”. The inclusion criteria in this study were full-text articles using the Randomized Controlled Trial (RCT) design from 2012 to 2022. The corresponding articles were then critically reviewed and analyzed using RevMan 5.3 software. Results: A meta-analysis was conducted on 9 randomized controlled trials (RCTs) from Belgium, Italy, Japan, Germany, Lithuania and Switzerland with a total sample of 537 stroke patients. The results of the meta-analysis showed that there was no difference in effectiveness between the use of robot assistive therapy and conventional therapy in improving the functional abilities of stroke patients' hands (SMD= -0.02; 95% CI= -0.42 to 0.38; p= 0.930). Conclusion: There is no difference in effectiveness between the use of assistive therapy robots and conventional therapy in improving the functional abilities of stroke patients' hands. Keywords: robot assistive therapy, stroke, hand functional abilities, meta-analysis Correspondence: Haris Sutopo, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: hartop4wd@gmail.com. Telepon: +628155010610.